Antena espiral equiangular para opera??es em grandes larguras de faixa - Fr?, Gabriel Lob?o da Silva (2016)
This work presents the study of spiral equiangular antenna applied as wideband irradiator element. A brief study about that geometry is presented. It appears in nature things and also at radiator elements applications. The equations was derived in order to evaluate such structures parameters. Some analysis from this model was made, searching the causes of its broadband performance. A few models are simulated establishing relationships between antenna's geometry and its radiation characteristics. A prototype was constructed with best results dimensions obtained through simulations. Two matching impedance structures were proposed, both of them developed by narrowing the width of a parallel strip transmission line. After several tests, it was decided to feed the prototype with no matching requirements, taking in to account that achieved radiation performance was good enough to meet expectations.